THE BASIC CONTENTS OF CONFUCIANISM IN THE HAN - NOM BOOK IN THE HISTORY OF VIETNAM - Van, Vu Hong (2022)
Confucianism originated in China and was spread into Vietnam in the 2nd century. During the process of existence and development, Confucianism was used by the feudal dynasties of Vietnam as the foundation of the superstructure, and become an effective tool in the management of the country. Confucianism has quickly penetrated into people's spiritual life, dominating all aspects of social life. Therefore, under the feudal dynasties of Vietnam, Confucianism used to hold an important position in fields such as politics, culture, history, etc. To spread the values of Confucianism, many documents about Confucianism have been printed and released; including documents on Han - Nom characters. Historically, documents of this kind have been very heavily printed and stored in the court and widely disseminated among the people. Through the ups and downs of history, these documents gradually disappear and are still very few today. These are valuable documents that help researchers to learn more clearly about the contents of Confucianism and its influence on history. Recognizing that importance, on the basis of studying Han - Nom documents on Confucianism still in existence up to this date, comparing and comparing with the works of previous, this study determined the contents of Confucianism recorded in Han - Nom documents, thereby determining the basic values of Confucianism and Han - Nom documents in history and present.